2021
DOI: 10.1111/are.15305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary inclusion of Bunium persicum, Bunium persicum essential oil on growth, immune components, immune‐related gene expressions and resistance to Aeromonas hydrophila , in rainbow trout, Oncorhynchus mykiss

Abstract: The immune-enhancing and antibacterial properties of Black cumin, Bunium persicum have been reported in the literatures. The present work examined the effects of black cumin essential oil (BEO) administration on immunity and resistance of rainbow trout, Oncorhynchus mykiss against the pathogen, Aeromonas hydrophila. To this end, fish were fed different levels of BEO [0%, 1% (10 g/kg diet), 2% (20 g/kg diet) and 3% (30 g/kg diet)] for 60 days. At the end of feeding trial, the growth parameters and immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Although the positive potentials of LR on fish growth has been reported in various studies (Gonçalves et al, 2011;Dawood et al, 2016;Xia et al, 2018;Sewaka et al, 2019;Hooshyar et al, 2020), there are few studies related to the effect of this probiotic in combination with herbs (Harikrishnan et al, 2010). The antioxidant system of fish is the first line against oxidative stress (Hoseinifar et al, 2020;Hajirezaee and Khanjani, 2021). Under oxidative stress conditions, antioxidant enzymes and related compounds protect cells against damages caused by free radicals.…”
Section: Discussionmentioning
confidence: 98%
“…Although the positive potentials of LR on fish growth has been reported in various studies (Gonçalves et al, 2011;Dawood et al, 2016;Xia et al, 2018;Sewaka et al, 2019;Hooshyar et al, 2020), there are few studies related to the effect of this probiotic in combination with herbs (Harikrishnan et al, 2010). The antioxidant system of fish is the first line against oxidative stress (Hoseinifar et al, 2020;Hajirezaee and Khanjani, 2021). Under oxidative stress conditions, antioxidant enzymes and related compounds protect cells against damages caused by free radicals.…”
Section: Discussionmentioning
confidence: 98%
“…Before gene expression assay, the method of Awad et al (2011) was used for the extraction of the RNA content from the kidney tissues (50 mg). After evaluating the quantity (spectrophotometrically at 260/280 nm) and quality (by electrophoresis on a 1.5% agarose gel) of the extracted RNA, 1 µg of RNA was allocated for the synthesis of cDNA [by previously designed qPCR primers (Table 1)] and then the expressions estimated by an iCycler (BioRad), as described in detail by Hajirezaee and Khanjani (2021).…”
Section: Immunological and Gene Expression Assaysmentioning
confidence: 99%
“…The immune response in aquatic organisms can be influenced by various factors, including the environment, feed availability, and the genetics of the broodstocks 1 , 15 . The study by Ekasari et al 16 has shown that the use of BFT can activate the immune response in shrimp species like the white-leg shrimp, depending on the sources and amounts of carbon applied in the BFT system.…”
Section: Introductionmentioning
confidence: 99%